O processo de socialização dos servidores na administração pública: o caso da Universidade Federal do Pampa UNIPAMPA - Berni, Rita de Cassia Durgante (2014)
This study was developed with the objective to identify the perception of the Universidade Federal do Pampa servers - UNIPAMPA in relation to the socialization process which participated during the admission into the institution. To achieve its purpose, this study had six specific objectives: to identify the processes and tools used in UNIPAMPA to the socialization of servers; characterize the profile of servers; identify the perception of the servers related to the organizational socialization process developed by UNIPAMPA; verify the perception of managers in the area of personnel management relating to the socialization process applied to servers; identify the actions of socialization provided by other Federal Institutions of Higher Education - IFES and finally propose subsidies to improve the socialization of the Universidade Federal do Pampa process servers - UNIPAMPA, in order to make better use of these skills in the performance of their professional activities. The research sought to contribute to the enrichment of processes related to the area of People Management in the public sphere studies, in order to provide people develop their intellectual, social and working potential. The study, from the proposed objectives, it was classified as descriptive in nature. Regarding this research method adopted was classified as a case study, with the object of analysis the Universidade Federal do Pampa - UNIPAMPA. This research method was chosen to be aligned with the proposed objectives and the research question that guided the study. How to approach the problem, we used both the qualitative method as the quantitative method. In the quantitative stage was used as a tool for data collection Organizational Socialization Inventory (ISO) proposed by Borges and others (2010). After a qualitative step, through semi-structured interviews with two managers in the area of personnel management relating to the socialization process applied to the servers who enter the institution was performed.